Pengaruh Kualitas Produk, Persepsi Harga, dan Word of Mouth Terhadap Keputusan Pembelian - Azizy, Fawaz; Hidayat, Ravindra Safitra (Economics and Digital Business Journal, 2024)
The high interest in the culinary business in Indonesia can be seen from the many cafes, restaurants and F&B franchises. Mixue Ice Cream & Tea is growing rapidly in Indonesia along with the increasing demand for ice cream and tea at affordable prices. The more Mixue franchise businesses, means more markets to reach and more customers. This makes the Mixue brand top of mind without huge marketing costs. This study aims to determine the effect of product quality, price perceptions and word of mouth on purchasing decisions. This study uses quantitative research methods through Non-Probability Sampling with Purposive Sampling techniques. The population used in this study are consumers who have or often come to Mixue Ice Cream and Tea Ciledug. The data used in this study are primary data obtained from questionnaires to 100 Mixue Ice Cream and Tea consumers. Data analysis of multiple linear regression analysis. The results of this study found that product quality, price perceptions, and word of mouth has a positive and significant effect on purchasing decisions